2020
DOI: 10.3389/fped.2020.00444
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Cough in Young Children: A Cohort Study

Abstract: Background and Objective: Data on the predictors of chronic cough development in young children are scarce. Our primary objective was to examine the factors associated with young children developing a chronic cough, with a focus on childcare attendance. Methods: A secondary analysis of data collected in a prospective cohort study of children presenting to three emergency departments and three primary healthcare centers in southeast Queensland, Australia. Eligible children where those aged <6-years presenting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Similar to the primary studies on the development of chronic cough [6,8,19], our study found that childcare attendance, young age, and a prior history of chronic cough were risk factors for PBB development. Amongst children in childcare, those who continued to attend while unwell with a cough illness were 13 times (adjusted odds ratio (OR) = 12.9, 95% CI 3.9, 43.3) more likely to develop chronic cough than those who remained absent [19].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to the primary studies on the development of chronic cough [6,8,19], our study found that childcare attendance, young age, and a prior history of chronic cough were risk factors for PBB development. Amongst children in childcare, those who continued to attend while unwell with a cough illness were 13 times (adjusted odds ratio (OR) = 12.9, 95% CI 3.9, 43.3) more likely to develop chronic cough than those who remained absent [19].…”
Section: Discussionsupporting
confidence: 84%
“…Similar to the primary studies on the development of chronic cough [6,8,19], our study found that childcare attendance, young age, and a prior history of chronic cough were risk factors for PBB development. Amongst children in childcare, those who continued to attend while unwell with a cough illness were 13 times (adjusted odds ratio (OR) = 12.9, 95% CI 3.9, 43.3) more likely to develop chronic cough than those who remained absent [19]. Moreover, when children with chronic wet cough undergoing bronchoscopy were compared with children undergoing bronchoscopy for indications other than a cough, those with PBB were more likely to have attended childcare (OR 8.4, 95% CI 2.3-30.5), although this effect was no longer significant on multivariable analyses [20].…”
Section: Discussionsupporting
confidence: 84%
“…For instance, some schools promote school attendance by rewarding individual children and school classes for good attendance and fining parents for child absences [ 53 ]. On the other hand, although the research about presenteeism among children is limited, there is evidence to suggest that presenteeism may adversely impact children’s health and education [ 15 , 16 ] as well as contributing to the spread of infection. More research is needed to explore the full extent of the health and educational effects of presenteeism among children.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with presenteeism in children have been less well explored. Outbreaks of infectious illnesses within educational settings are common, particularly in England’s primary schools [ 14 ], which can lead to increased rates of hospital attendance among children [ 15 ], impacting children’s health and education. One study in Peru, among university students also found a significant association between presenteeism and reduced academic performance, which had a greater effect size than the impact of absenteeism on academic performance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nesti and Goldbaum stated that the risk of infection among children at preschool education centers has increased 2-3 times, which is a significant issue in terms of both personal health and community health [4]. Several other studies indicate the prevalence of infectious diseases and the increased risk of infection at preschool education institutions [5][6][7][8][9][10][11][12][13][14][15][16]. They are identified as a risk factor in the spread of infectious diseases; however, the solution to this risk does not involve keeping children away from them.…”
Section: Introductionmentioning
confidence: 99%